Efforts by the Peatland and Mangrove Restoration Agency to Foster Environmental Awareness Among Students in Dumai City - Sugiyanto, Seger (Lembaga penelitian dan pengabdian kepada Masyarakat, 2024)
Forest and peatland fires, as well as coastal abrassion, are environmental issues that require serious attention. This study aims to analyze the efforts made by the Peatland and Mangrove Restoration Agency in building ecological awareness, specifically regarding peatland and mangrove ecosystems. The research employs qualitative methods through interviews, observations, documentation, and literature review. The findings indicate that the Peatland and Mangrove Restoration Agency's efforts to promote environmental awareness involve a collaborative approach to socialization and education. The Agency collaborates with the Dumai City Government, particularly the Department of Education, in the Pancasila Student Profile Strengthening Project (P5). Learning about peatland and mangrove ecosystems is incorporated as a local content highlight in the P5 curriculum. Dumai has even become the first region in Riau Province to launch the P5 Peatland and Mangrove Curriculum. Policy interventions in educational institutions are latent efforts aimed at fostering a love for the environment concerning peatland and mangrove ecosystems and ensuring future conservation. This effort is crucial due to the increasing potential loss of peatland ecosystems in Dumai City as a result of land conversion for industrial areas. Similarly, the problem of abrassion is increasingly alarming due to the degradation of mangrove ecosystems, both from natural causes and human activities.